A benefit-cost framework for early intervention to prevent sex trading. Issue 1 (17th April 2015) - Martin, Lauren; Lotspeich, Richard
Abstract: Prevention of juvenile sex trading in the US has risen to prominence in public policy discourse. We develop a generalized benefit-cost model to shed light on this policy issue and illustrate the framework with a case study from Minnesota. The model treats government-funded intervention as an investment project and calculates its net present value. Benefits are derived from harms avoided by reducing the extent of sex trading. The impacts of youth involvement in the market for sexual services are highly complex, and clear data on them are lacking. To account for empirical ambiguity we develop the model around a representative individual, approximate the effect of intervention on the sex market, and conduct sensitivity analysis with key model parameters. The case study evaluates seventeen distinct harms caused by sex trading based on conservative best estimates from scholarly literature. We find a large positive Net Present Value, suggesting it is in the best interest of Minnesota taxpayers to support intervention.